To Ban or Not to Ban? Reviewing an Ongoing Dilemma on Sea Turtle Egg Trade in Terengganu, Malaysia - Mohd Jani, Jarina; Jamalludin, Muhammad Allim; Long, Seh Ling (Frontiers in Marine Science, 2020)
Legal trade in sea turtles and their eggs remains a reality in many countries where conservation of this marine endangered species does exist. This duality is a conflict to some who appeal for a total trade ban, which may have implications on local livelihoods. Using the Sustainable Livelihoods Approach (SLA), this paper considers the dilemma by empirically examining the context of the state’s legislation, particularly the Terengganu Turtle Enactment (TTE) and its “haves” – what is legally provided on paper, the available capitals in hand, and the actual implementation carried out in practice – to elucidate whether a trade ban is indeed the immediate solution for improving sea turtle conservation in the state of Terengganu, Malaysia, which is an important rookery in Southeast Asia. Findings based on data collected through extensive archival research and in-depth interviews with officers of the state who manage sea turtles as well as those whose past and current livelihoods depend on the trade indicate that (1) sea turtles are a transformative natural capital that the Terengganu legislation supports on paper via a pro-conservation concession system; (2) in putting paper into practice, those involved in its implementation have strategically mobilized available resources to achieve a balanced outcome between conservation and livelihood; and (3) institutional absenteeism, financial handicap, and ambiguous legal protection status of nesting beaches are issues that need addressing to fulfill the true potential of this legislation. However, a better conservation outcome is administratively possible via a full conservation–concession system that lists all beaches under the TTE to ensure the sustainability of sea turtles and local livelihoods, in preparation for the ultimate long-term goal: total conservation via a trade ban without which conservation of the species remains precarious not only at state but also at national and regional levels.